Ground glass opacity resection extent assessment trial (GREAT): A study protocol of multi-institutional, prospective, open-label, randomized phase III trial of minimally invasive segmentectomy versus lobectomy for ground glass opacity (GGO)-containing early-stage invasive lung adenocarcinoma - Li, Hanyue; Wang, Yiyang; Chen, Yang; Zhong, Chenxi; Fang, Wentao (Frontiers in Oncology, 2023)
Background With widely use of computed tomography (CT) screening, an increasing number of early-stage lung cancers appearing as ground glass opacity (GGO) have been detected. Therefore, attempts have been made to investigate the feasibility of segmentectomy instead of lobectomy for those patients with GGO. However, the two recently released phase III trials failed to distinguish between GGO-containing lesions from pure solid nodules in the inclusion criteria, and the surgical methods did not distinguish between minimally invasive surgery and open thoracotomy. In addition, total lesion size≤ 2cm was taken as the inclusion criterion, instead of the solid part size recommended in the eighth edition of Union for International Cancer Control/ International Association for the Study of Lung Cancer/American Joint Committee on Cancer (UICC/IASLC/AJCC) staging system. Hence, this present trial aims to figure out whether minimally invasive segmentectomy shows superiority in perioperative outcomes and non-inferiority in oncological prognosis over minimally invasive lobectomy among patients with GGO-containing clinical stage T1a-T1b lung invasive adenocarcinoma (IADC). Methods/Design Sample sizes are 1024 patients, who will be randomized into minimally invasive segmentectomy and lobectomy groups. Patients will be collected from 19 hospitals in China. Patients with peripheral mixed ground glass opacity (mGGO) with 0.5cm